Developing national outcome standards for the management of gonorrhoea and genital chlamydia in genitourinary medicine clinics. Issue 3 (28th May 2004) - Low, N; Welch, J; Radcliffe, K
Abstract : Background: Measuring clinical performance within a framework of clinical governance is increasingly important for monitoring improvements in patient care. Standards for quality indicators must, however, be achievable and evidence based. We describe an approach to the development of national standards for measuring outcomes of care for gonorrhoea and genital chlamydia in genitourinary medicine clinics. Methods: Two standards for each infection, one reflecting quality of case management and one reflecting partner management were chosen by consensus. A systematic review of published and unpublished UK studies about gonorrhoea and chlamydia management was carried out and weighted averages calculated for each parameter, stratified by location. Genitourinary medicine practitioners around the country were also asked for their opinion about desirable values for each standard and the results compared. Variability in performance between centres was examined using Shewhart's control charts. Results: We identified 17 reports about gonorrhoea outcomes and 14 about chlamydia. There was marked heterogeneity in results according to geographical location and different standards were set for clinics in and out of London. Opinions from practitioners suggested much higher standards than the values obtained from the systematic review. There was evidence for special cause variation related to management of gonorrhoea and chlamydia in London clinics. Conclusions: Standards set using expert opinion are unrealistic when compared to evidence of what is achievable. Evidence based methods should therefore be used to derive outcome standards for case management gonorrhoea and chlamydia. The control chart method identified clinics where investigation to find reasons for special cause variation in performance should be undertaken to change practice.